2014
DOI: 10.1590/s0104-12902014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and tuberculosis in Rio de Janeiro

Abstract: This paper aims at understanding social causality of Tuberculosis in Rio de Janeiro. This is one of the Brazilian states with the highest incidence of this disease. We follow the story of Paulo, a patient who received care at the outpatient clinic for multi-drug resistant Tuberculosis, in Rio de Janeiro. To make sense of his story, we will look at it through the concept of vulnerability in life conditions. Along with Sabroza (2006), we argue that this vulnerability is a collective expression of the economic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
1
0
1
Order By: Relevance
“…In contrast, in a study in Porto Alegre, TB/HIV co-infection did not reach only the periphery, a fact demonstrated by high rates in neighborhoods that have better living conditions. In that study, the authors identified two perspectives for the occurrence of TB, a traditional one related to misery and to those socially excluded, and co-infection with HIV and AIDS, which encompasses other population groups 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a study in Porto Alegre, TB/HIV co-infection did not reach only the periphery, a fact demonstrated by high rates in neighborhoods that have better living conditions. In that study, the authors identified two perspectives for the occurrence of TB, a traditional one related to misery and to those socially excluded, and co-infection with HIV and AIDS, which encompasses other population groups 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Brás (2014), é recente a importância dada aos aspectos socioeconômicos, relacionando como um dos determinantes de maior incidência de tuberculose. O uso de políticas públicas específicas é primordial para amenização desta condição social.…”
Section: Introductionunclassified